PROMOTING FIRM PERFORMANCE VIA BOARD OF DIRECTORS EFFECTIVENESS : A STUDY OF FINANCIAL SERVICES COMPANIES IN NEW ORLEANS - Shahad Salim (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study explores the critical link between board effectiveness and company performance, focusing on New Orleans' financial services sector. In today's dynamic business landscape, boards of directors play a pivotal role in guiding organizations towards sustainable growth and value creation. The research aims to contribute significantly to the corporate governance discourse by introducing novel metrics such as cash flow and value-added production, expanding the scope of analysis beyond traditional financial indicators. We emphasize two key factors: gender diversity and director tenure, offering a holistic understanding of board composition. The empirical analysis draws from a dataset of financial services firms in New Orleans, revealing that boards with gender diversity and experienced directors excel in strategic decision-making, risk management, and innovation. This highlights the importance of building diverse and knowledgeable boards that blend seasoned business leaders with fresh perspectives. The findings hold broader implications for policymakers, who can advocate for policies promoting diversity and experience in corporate governance. Investors gain insights into value drivers beyond traditional metrics, facilitating partnerships with companies prioritizing comprehensive performance improvement. The study illuminates the intricate relationship between board effectiveness and company success in New Orleans' financial services sector. The unique methodology combines innovative performance indicators and an integrated framework, providing a comprehensive view of the value created by diverse and experienced boards. These insights inform investment strategies, policy development, and strategic decision-making, fostering long-term company performance and societal benefit.